Abstract: This research is aimed to find out whether Reciprocal Teaching Technique effective in teaching reading narrative text. This research was conducted to eighth graders of SMPN 11 Sepauk in 2014/2015. The population is 68 students with class VIII A - Irawan, Robertus Umi; Bunau, Eusabinus; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research is aimed to find out whether Reciprocal Teaching Technique effective in teaching reading narrative text. This research was conducted to eighth graders of SMPN 11 Sepauk in 2014/2015. The population is 68 students with class VIII A of 32 students as sample by using cluster sampling. The researcher conducted a pre-experimental research. The data was collected by using measurement technique. Essay test was used in collecting data. Data was collected by administering pre-test, giving treatment, administering post-test, and analyzing the test result with t-test score (7.47) was higher than t-table (1.69) at 0.05 confidence level. The result showed mean score of pre-test was 35.15 and post-test 55.78 and difference scores pre-test and post-test was 20.63. It means the Alternative Hypothesis (Ha) that saying the use of reciprocal teaching technique is effective in teaching reading narrative text to the eight grade students of SMPN 11 Sepauk is accepted. Keywords: Reciprocal Teaching Technique, Teaching Reading, Narrative Text. Abstrak: Penelitian ini bertujuan untuk menemukan apakah tehnik Reciprocal Teaching efektif untuk pengajaran membaca teks narasi. Penelitian ini diberlakukan kepada siswa kelas delapan SMPN 11 Sepauk tahun ajaran 2014/2015. Populasi dalam penelitian ini terdiri dari 68 siswa dengan kelas 8A yang terdiri dari 32 siswa sebagai sampel, dipilih dengan menggunakan cluster sampling. Peneliti menggunakan metode pre-eksperimental dalam penelitiannya. Data dikumpulkan dengan menggunakan teknik ukuran. Tes esei digunakan sebagai alat untuk mengumpulkan data. Data dikumpulkan dengan cara mengatur pre-test, memberikan penanganan, mengatur post-test, dan menganalisis hasil tes dengan nilai t-test (7,47) dimana hasilnya menunjukkan nilai yang lebih tinggi dibandingkankan dengan t-table (1,69) pada kenyamanan penelitian dengan tingkat kesalahan 0,05. Hasil dari penelitian ini menunjukkan nilai rata-rata dari pre-test ialah 35,15 dan nilai rata-rata dari post-test ialah 55,78 sedangkan perbedaan antara keduanya adalah 20,63. Ini berarti bahwa pernyataan Alternative Hypothesis (Ha) yang menyatakan penggunaan reciprocal teaching technique efektif untuk digunakan dalam pengajaran membaca teks narasi kepada siswa kelas delapan SMPN 11 Sepauk dapat diterima. Kata Kunci: Teknik Mengajar Reciprocal, Pengajaran Membaca, Teks Narasi.